THE INFLUENCE OF STORE LOCATION AND STORE ATMOSPHERE ON COSTUMER SHOPPING BEHAVIOR OF MULTI MART MANADO - Mokalu, Christy; Mekel, Peggy Adeline (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
In this Post-Modern era, the costumer expectation of a retail store are develop. To compensate the market development and satisfy the costumer needs and wants, the marketers have to create a new concept of a store that can give a new shopping experience. The objectives of this research are to analyze the influence of Store Location and Store Atmosphere of Costumer Shopping Behavior of Multi Mart Paal 2. This research is conduct in Manado. This research is a causal type of research where investigate the influence of store location and store atmosphere on costumer shopping behavior and using a multiple regression model to answer the research problem.  The population of this study is a costumer of Multi Mart Paal 2 in Manado with sample taken by 100 respondent. In the hypothesis testing, this research conduct a conclusion where there is a simultaneously and  significantly influence of store location and store atmosphere on costumer shopping behavior of Multi Mart Paal 2. Partially, the store location have most influencing on costumer shopping behavior and store atmosphere have least influencing on costumer shopping behavior. This study approve that for post-modern peoples just like in Manado, a location and atmosphere of a store will affect the costumer shopping behavior, where they mental decision decide to do their shopping efficiently in a store who have easy transport access with good combination of attractive storefront, good service, and comfortable atmosphere.   Keywords: post-modern, store location, atmosphere, behaviour.